Pengaruh Desain Exterior Terhadap Kesakralan Masjid, Studi Kasus : Masjid Keuchik Leumik, Banda Aceh - Mira Alfitri (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
The meaning of the sacred is related to holy things, religious, holiness and majesty. The sacred is closely related to houses of worship such as mosques. In its design, the exterior design is very influential in providing the first impression of the sacred value. The Keuchik Leumik Mosque was chosen as the object of research because it is one of the most beautiful mosques in Banda Aceh, so it has an interesting exterior design to study. The sacred is studied in several aspects, namely symbolism, orientation, ornamentation, layout, color and material.